Exploring the digesta- and mucosa-associated microbial community dynamics in the rumen and hindgut of goats from birth to adult - Li, Bibo; Yin, Weiqi; Lei, Mingkai; Wang, Xiaolong; Yang, Yuxin; Zhang, Chunxiang; Chen, Yulin (Frontiers in Microbiology, 2023)
Recently, the relationship between the goat host and its gastrointestinal microbiome has emerged as a hallmark of host-microbiota symbiosis, which was indispensable for the proper physiological function that convert the plant biomass to livestock products. However, little integrative information about the establishment of gastrointestinal microflora in goats exists. Herein, we characterized the colonizing process of the bacterial community in the digesta and mucosa of the rumen, cecum, and colon of the cashmere goat from birth to adulthood to compare its spatiotemporal difference via 16S rRNA gene sequencing. A total of 1,003 genera belonging to 43 phyla were identified. Principal coordinate analysis unveiled the similarity of microbial community between or within each age group increased and gradually developed toward mature whatever in digesta or mucosa. In the rumen, the composition of the bacterial community in digesta differed significantly from in mucosa across age groups; whereas in the hindgut, there was a high similarity of bacterial composition between the in digesta and mucosa in each age group before weaning, while the bacterial community structure differed markedly between these two types of samples after weaning. Taxonomic analysis indicated that 25 and 21 core genera coexisted in digesta and mucosa of the rumen and hindgut, respectively; but their abundances differed considerably by GIT region and/or age. In digesta, as goats aged, a lower abundance of Bacillus was observed with higher abundances of Prevotella 1 and Rikenellaceae RC9 in the rumen; while in the hindgut, the genera Escherichia-Shigella, Variovorax, and Stenotrophomonas decreased and Ruminococcaceae UCG-005, Ruminococcaceae UCG-010, and Alistipes increased with age increased. In mucosa, the rumen showed microbial dynamics with increases of Butyrivibrio 2 and Prevotellaceae UCG-001 and decreases of unclassified_f_Pasteurellaceae; while the genera Treponema 2 and Ruminococcaceae UCG-010 increased and Escherichia-Shigella decreased in the hindgut as goats aged. These results shed light on the colonization process of microbiota in the rumen and hindgut, which mainly include the initial, transit, and mature phases. Furthermore, there is a significant difference in the microbial composition between in digesta and mucosa, and both these exhibit a considerable spatiotemporal specificity.